EVALUASI KEEKONOMIAN KERJA ULANG PINDAH LAPISAN DENGAN METODE PERFORASI SUMUR PRODUKSI - Susilo, Arya Cahya; Afifah, Rohima Sera; Randanan, Eltimeyansi Chrisye; Willard, Karnila; Sulardi, Sulardi (INFO-TEKNIK, 2020)
The problem is that there is no certainty about the production capacity of the wells before evaluating the performance of production wells. The research objective was to describe the condition of oil and gas reserves in production wells and an economic picture of the MBR production resources after the recovery period by moving layers using the perforation method. This study used a used research method with a case study approach, namely the case that occurred in the MBR production well of PT. Medco E&P Tarakan operation area. The results of the evaluation of production capacity after displacement recovery based on the analysis of logging data at a depth of 850 MZ, it is known that the initial oil reserves (OOIP) are 284,304 STB with a recovery factor of 25%. The results of the calculation of the economic indicator for the proposed perforation of work to move layers, the total value of NPV. 15% was obtained in the eighth month in total lifting of 28,466, namely USD 123.561, the payout time for this work was 1.8 months with an IRR of 340% indicating that investment has the potential to provide benefits.